2013
DOI: 10.1088/2041-8205/770/2/l36
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Solar Magnetic Elements Up to Supergranular Spatial and Temporal Scales

Abstract: The study of the spatiotemporal scales on which small magnetic structures are organized, may be approached by determining how magnetic elements are transported by convective motions. The process involved is diffusion. Several works explored the topic, both by simulations and observations. In order to constrain the diffusion process, we analyze the displacement of magnetic elements in time, and the evolution of the mutual distance between magnetic element pairs. We take advantage of Hinode high spatial resoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 71 publications
4
58
0
2
Order By: Relevance
“…This assumption has been verified in the quiet Sun Giannattasio et al 2013) where high values of β are observed. In a Lagrangian approach, the trajectories of single magnetic elements are employed for a statistical determination of the dynamical properties of the ensemble.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…This assumption has been verified in the quiet Sun Giannattasio et al 2013) where high values of β are observed. In a Lagrangian approach, the trajectories of single magnetic elements are employed for a statistical determination of the dynamical properties of the ensemble.…”
Section: Introductionmentioning
confidence: 62%
“…2 was realized by computing the displacement of magnetic elements from the long-duration (∼25 h) data set acquired by Hinode-NFI (Kosugi et al 2007;Tsuneta et al 2008) and used in the analysis by Giannattasio et al (2013Giannattasio et al ( , 2014a. The spatial resolution of this data set is 0.…”
Section: Real Datamentioning
confidence: 99%
See 2 more Smart Citations
“…By analyzing the same data set, Giannattasio et al (2013) found that the equipartition magnetic flux density is B e 255 G. Only less than 4% of the total magnetic elements have an average flux greater than that value, and are all located in the network. Therefore, the condition of passive magnetic elements is reasonably fulfilled in the internetwork regions, as demonstrated by the spectro-polarimetric studies performed by Orozco Suárez et al As done in the previous works in the literature (see, e.g., Lepreti et al 2012) the separation spectrum Δr 2 was first computed for all the pairs of magnetic elements, regardless of their initial separation.…”
Section: Resultsmentioning
confidence: 99%